2009
DOI: 10.1111/j.1460-9568.2009.06952.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin /orexin contributes to the expression of some but not all forms of stress and arousal

Abstract: Hypocretin/orexin has a well-established role in wakefulness and in the maintenance of arousal. Because stress is associated with arousal, it has been proposed that hypocretin is also involved in stress. However, it is not clear if this is true for all forms of stress. To clarify this issue, we compared four conditions combining high arousal with no or low stress (wakefulness and exploration) or high stress (contextual fear and restraint) in the rat. We looked at Fos expression in hypocretin neurons, hypocreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
120
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 40 publications
10
120
3
Order By: Relevance
“…In mammals, the HCRT neurons receive abundant projections from the amygdala (Winsky-Sommerer et al, 2004;Zhang et al, 2009;Sakurai and Mieda, 2011), a key component of the fear response pathway, and innervate the PVN , which regulates stress and anxiety via the hypothalamic-pituitaryadrenal axis. In agreement with this idea, in HCRT knock-out and HCRT neuron-ablated transgenic mice, emotional stresses generate attenuated responses of locomotor activity, as well as blood pressure, heart rate, and cardiorespiratory responses (Kayaba et al, 2003;Furlong et al, 2009;Zhang et al, 2009). In zebrafish, we found that deficiency in the response to external stimuli is not specific to light and was also observed in the larvae reaction to sound stimuli.…”
Section: Discussionsupporting
confidence: 48%
“…In mammals, the HCRT neurons receive abundant projections from the amygdala (Winsky-Sommerer et al, 2004;Zhang et al, 2009;Sakurai and Mieda, 2011), a key component of the fear response pathway, and innervate the PVN , which regulates stress and anxiety via the hypothalamic-pituitaryadrenal axis. In agreement with this idea, in HCRT knock-out and HCRT neuron-ablated transgenic mice, emotional stresses generate attenuated responses of locomotor activity, as well as blood pressure, heart rate, and cardiorespiratory responses (Kayaba et al, 2003;Furlong et al, 2009;Zhang et al, 2009). In zebrafish, we found that deficiency in the response to external stimuli is not specific to light and was also observed in the larvae reaction to sound stimuli.…”
Section: Discussionsupporting
confidence: 48%
“…The descending pathways mediating the DMH-evoked increase in respiratory activity may involve chemosensitive orexin neurons. In support of this hypothesis, microdialysis of CO 2 -enriched fluid (25% CO 2 ) into the orexin neuron-rich DMH/ perifornical region of the hypothalamus increases resting activity (26), and activation of hypothalamic orexin neurons produces defense-like or panic-like cardiorespiratory responses (17,21,22). Descending orexin projections to the RTN-pFRG region, located in the ventral medulla and intimately related to the central command of respiration, have also been identified (25).…”
Section: Role Of the Dmh And Nts 5-ht 3 Receptors In The Respiratory mentioning
confidence: 86%
“…In orexin knockout mice, the cardiovascular and respiratory responses evoked by disinhibition of the DMH/PeF are greatly reduced compared with responses in wild-type mice (87,164). Similarly, systemic administration of the dual orexin receptor antagonist Almorexant reduces the cardiovascular responses associated with arousal and psychological stress but not those associated with cold stress, a physical stressor (63). In addition, the increases in arterial pressure, heart rate, renal sympathetic nerve activity, and respiratory rate evoked by disinhibition of neurons in the PeF and DMH are reduced by about 50% after systemic administration of Almorexant (80).…”
Section: Role Of Dmh and Pef In Integrating Stress-evoked Responsesmentioning
confidence: 95%
“…Psychological stressors can be further subdivided into conditioned stressors (i.e., ones that are normally innocuous but which are perceived as threatening because of previous experiences) or unconditioned stressors (i.e., ones that are intrinsically threatening, such as the sight, sound, or odor of a predator). Physical and psychological stressors activate different populations of neurons in the brain (44,63,102). Similarly, there is evidence that the autonomic responses to conditioned and unconditioned psychological stressors are also mediated by different pathways in the brain (62).…”
mentioning
confidence: 99%